PENINGKATAN KINERJA USAHA MELALUI PENGUATAN PEMBELAJARAN KEWIRAUSAHAN DAN PERILAKU PROAKTIF KEUANGAN PELAKU USAHA MONEL - Anna Widiastuti; Sulis Tari; Sania Septi F (Jurnal Dinamika Ekonomi & Bisnis, 2021)
AbstractThis study aims to determine the effect of entrepreneurial learning, which is seen from the individual learning approach and collective learning and financial proactive behavior on business performance. Research respondents are monel handicraft business actors in Jepara district, Central Java. By using multiple regression analysis, it is found that individual learning has a significant effect on proactive financial behavior, while collective learning has no significant effect on financial proactive behavior. And, financial proactive behavior also has a significant influence on the realization of business financial performance